2011
DOI: 10.1038/clpt.2011.142
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Rate-Determining Process in the Hepatic Clearance of Atorvastatin in a Clinical Cassette Microdosing Study

Abstract: Clearance of atorvastatin occurs through hepatic uptake by organic anion transporting polypeptides (OATPs) and subsequent metabolism by cytochrome P450 (CYP) 3A4. To demonstrate the relative importance of OATPs and CYP3A4 in the hepatic elimination of atorvastatin in vivo, a clinical cassette microdose study was performed. A cocktail consisting of a microdose of atorvastatin along with probe substrates for OATPs (pravastatin) and CYP3A4 (midazolam) was orally administered to eight healthy volunteers. The pharm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(178 citation statements)
references
References 33 publications
14
164
0
Order By: Relevance
“…A single oral dose of 600-mg rifampin greatly increased the AUCs of pitavastatin (Chen et al, 2013, Prueksaritanont et al, 2014, Prueksaritanont et al, 2017, Takehara et al, 2018, rosuvastatin (Prueksaritanont et al, 2014, Prueksaritanont et al, 2017, Wu et al, 2017, Takehara et al, 2018 and atorvastatin (Lau et al, 2007, He et al, 2009, Maeda et al, 2011, Prueksaritanont et al, 2017, Takehara et al, 2018) by 2.8-to 6.7-fold, 3.0-to 4.7-fold, and 4.6-to 12.0-fold, respectively, in multiple clinical DDI studies. In agreement, the administration of 600-mg rifampin in this study resulted in a 2.8-to 3.7-fold elevation in CPI AUC(0-24h) and a 2.…”
Section: Discussionmentioning
confidence: 94%
“…A single oral dose of 600-mg rifampin greatly increased the AUCs of pitavastatin (Chen et al, 2013, Prueksaritanont et al, 2014, Prueksaritanont et al, 2017, Takehara et al, 2018, rosuvastatin (Prueksaritanont et al, 2014, Prueksaritanont et al, 2017, Wu et al, 2017, Takehara et al, 2018 and atorvastatin (Lau et al, 2007, He et al, 2009, Maeda et al, 2011, Prueksaritanont et al, 2017, Takehara et al, 2018) by 2.8-to 6.7-fold, 3.0-to 4.7-fold, and 4.6-to 12.0-fold, respectively, in multiple clinical DDI studies. In agreement, the administration of 600-mg rifampin in this study resulted in a 2.8-to 3.7-fold elevation in CPI AUC(0-24h) and a 2.…”
Section: Discussionmentioning
confidence: 94%
“…All of these results suggested that the enhanced activity and expression of hepatic Cyp3a were the main contributors to the increases in systemic clearance of simvastatin and simvastatin acid. The uptake of drugs by hepatocytes is also considered a rate-determining process in the hepatic clearance of statins via OATPs [33,34] . The uptake of simvastatin by hepatocytes and the expression of Oatp2 were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Uptake of simvastatin by hepatocytes Uptake of statins by hepatocytes is considered a ratedetermining process in the overall hepatic elimination of statins [33,34] . The uptake of simvastatin by hepatocytes was investigated using freshly isolated rat hepatocytes from experimental rats ( Figure 3D).…”
Section: Pharmacokinetics Of Simvastatin In Dm Rats After Oral and Inmentioning
confidence: 99%
“…We further tried to show the rate-limiting step of hepatic clearance of OATP substrates directly in vivo in humans by a cocktail microdosing clinical study. 21) In this study, atorvastatin was selected as a model compound since it is a substrate of both OATPs and CYP3A4. In the first period, a cocktail of microdose (each 33 µg) of atorvastatin, pravastatin (OATP1B1 probe substrate) and midazolam (CYP3A4 probe substrate) was administered to healthy volunteers and the plasma concentrations of these drugs were monitored.…”
Section: Ps CL β Ps Ps Clmentioning
confidence: 99%